Inhibition of Endothelial NOTCH1 Signaling Attenuates Inflammation by Reducing Cytokine-Mediated Histone Acetylation at Inflammatory Enhancers. Issue 4 (April 2018) - Poulsen, Lars la Cour; Edelmann, Reidunn Jetne; Krüger, Stig; Diéguez-Hurtado, Rodrigo; Shah, Akshay; Stav-Noraas, Tor Espen; Renzi, Anastasia; Szymanska, Monika; Wang, Junbai; Ehling, Manuel; Benedito, Rui; Kasprzycka, Monika; et al.
Abstract : Objective—: Endothelial upregulation of adhesion molecules serves to recruit leukocytes to inflammatory sites and appears to be promoted by NOTCH1; however, current models based on interactions between active NOTCH1 and NF-κB components cannot explain the transcriptional selectivity exerted by NOTCH1 in this context. Approach and Results—: Observing that Cre/Lox-induced conditional mutations of endothelial Notch modulated inflammation in murine contact hypersensitivity, we found that IL (interleukin)-1β stimulation induced rapid recruitment of RELA (v-rel avian reticuloendotheliosis viral oncogene homolog A) to genomic sites occupied by NOTCH1-RBPJ (recombination signal-binding protein for immunoglobulin kappa J region) and that NOTCH1 knockdown reduced histone H3K27 acetylation at a subset of NF-κB–directed inflammatory enhancers. Conclusions—: Our findings reveal that NOTCH1 signaling supports the expression of a subset of inflammatory genes at the enhancer level and demonstrate how key signaling pathways converge on chromatin to coordinate the transition to an infla mmatory endothelial phenotype. Abstract : Supplemental Digital Content is available in the text.